Note from the Editor-in-Chief - Sing, Alexandra (Consilience, 2013)
Dear Readers, It is my great pleasure to announce the publication of our 9th Issue. Our editorial and managing teams have worked diligently over the past few months to compile a collection of articles we believe effectively address topics trending in sustainable development today. As Editor-in-Chief, I would like to extend my appreciation to our editors and supporting boards for their tireless efforts in producing another critical asset to the field of sustainable development. This season’s issue features a variety of articles attending to topics ranging from sustainable agriculture, urban planning, climate change, and development initiatives, among others. We are particularly excited to present Professor Douglas Kelbaugh’s opinion piece on “The Environmental Paradox of Cities.” In this article, Professor Kelbaugh presents new ways of thinking about the impact that densely inhabited urban zones have on the local and global environment. In addition to several provocative opinion pieces, Issues IX also features several scholarly articles, photo essays, and a field note. In one of our featured scholarly articles, Damilola Olawuyi addresses a timely topic through her discussion of the impacts of major oil spills. For those who followed our coverage of the systematic contamination of the Ecuadorian Amazon by Texaco, this article may be of particular interest. Our featured field note, by Angelica Patterson, focuses on the topic of climate change through the lens of a local case study based in New York State’s Black Rock Forest. Finally, we have included a collection of photo essays, which we hope will give human value to the topics we discuss. The mission of Consilience has always been to initiate dialogue on issues in sustainable development. We hope that, through engagement, our readers, editors, and authors can come together in some capacity to discuss solutions to the many problems threatening sustainable development. The interdisciplinary nature of our publication is a deliberate attempt to illustrate the range of people, institutions, and systems unsustainable practices affect. Yet, through collective action, we can find solutions to address some of our planet’s most pressing communal problems. It is our hope that Consilience can play some small role in setting this communal awareness and cooperation in motion. I invite you to read Issues IX as well as our past publications and Briefings Column. As always, please contact me with any questions, critiques, feedback or submissions at contact@consiliencejournal.org. Regards, Alexandra Sing Editor-in-Chief Consilience: The Journal of Sustainable Development